The retarded child : answers to questions parents ask - Attwell, Arthur A.; Clabby, Ann (Burbank, California : Eire Press, 1969)
Children have always existed, and perhaps always will who, from illness, birth injury, congenital or genetic causes, are mentally retarded. This are has long been of concern to medicine, psychology, and more recently education; but for some reason has not been of great concern to the general public.
1. What is mental retardation -- 2. The why of mental retardation -- 3. Diagnosis and referral -- 4. The M.A and the I.Q -- 5. Family relationships: Problems and adjustments -- 6. Family relationships: The child -- 7.Speech -- 8. Schooling -- 9. Parent organizations -- 10. Sex education -- 11. Institutionalization -- 12.Vocational planning.
Includes index.
Keywords: CHILDREN WITH MENTAL DISABILITIES